Smart taxi security system design with internet of things (IoT) - Indrianto Indrianto; Meilia Nur Indah Susanti; Riki Ruli A. Siregar; Purwati Putri J.; Yudhi Purwanto (Universitas Ahmad Dahlan, 2019)
Safety is an important thing in driving. Security in driving is aimed at the way of driving the vehicle or the security on the vehicle itself. Vehicle assets, especially cars, that are quite expensive or luxurious assets Therefore, safety protections for such vehicles are necessary. Taxi is a valuable asset for the company. To maintain the asset, a good security system is needed. With a good security system, the asset will be protected and the investments invested will not be reduced. By using the prototype method, a tool will be made in accordance to the wishes of the user. The Encludean distance method is used to calculate the distance of the incident and the nearest police station. By using the progress of technology, the progress can be utilized to help the security of taxi owned by a company or personal (online). The purpose of this study is to create a tool that can secure the taxi and its driver of crimes that might occur. IoT (internet of things) can help to secure a taxi since it is able to locate the incident’s location precisely and accurately.